Evaluation of wetting transitions on injected molded hierarchical moss structures - Borůvka, Martin; Janeba, Martin (Univerzita Pardubice, 2013)
Bio-inspired hierarchical surfaces demonstrate a potential for a variety of green technologies. The design of those surfaces remains a challenging scientific and technological task. The diversity of plant surface structures, evolved over 460 million years, has led to a large variety of highly adapted functional structures. The plant cuticle provides structural, chemical and physical modifications for surface wetting, ranging from superhydrophilic to superhydrophobic. Understanding the physical mechanism of wetting transitions is crucial for the design of those biomimetic surfaces. In this paper is investigated hydrophilic surface structure of moss. Enlarged structures is replicated on cavity insert in a mold base of standard two plates tooling core. Using different types of polar and non-polar termoplastic polymers were injected testing specimens than were evaluated wetting transitions by different types of liquids.
Keywords: biomimetic; wetting transitions; termoplastic polymers; injection molding